Forensic DNA biology : a laboratory manual - Elkins, Kelly M. (London: Elsevier, 2013)
A collection of forensic DNA typing laboratory experiments designed for academic and training courses at the collegiate level --
Includes bibliographical references and index.
Keywords: Forensic genetics; DNA fingerprinting; DNA Fingerprinting -- Laboratory Manuals; Forensic Genetics -- methods -- Laboratory Manuals; Polymerase Chain Reaction -- Laboratory Manuals; Sequence Analysis, DNA -- methods -- Laboratory Manuals